Healthcare Expenditure and Productivity Cost Savings from Reductions in Cardiovascular Disease and Type 2 Diabetes Associated with Increased Intake of Cereal Fibre among Australian Adults: A Cost of Illness Analysis - Fayet-Moore, Flavia (Nutrients, 2018)
An ageing population and growing prevalence of chronic diseases including cardiovascular disease (CVD) and type 2 diabetes (T2D) are putting increased pressure on healthcare expenditure in Australia. A cost of illness analysis was conducted to assess the potential savings in healthcare expenditure and productivity costs associated with lower prevalence of CVD and T2D resulting from increased intake of cereal fibre. Modelling was undertaken for three levels of increased dietary fibre intake using cereal fibre: a 10% increase in total dietary fibre; an increase to the Adequate Intake; and an increase to the Suggested Dietary Target. Total healthcare expenditure and productivity cost savings associated with reduced CVD and T2D were calculated by gender, socioeconomic status, baseline dietary fibre intake, and population uptake. Total combined annual healthcare expenditure and productivity cost savings of AUD$17.8 million–$1.6 billion for CVD and AUD$18.2 million–$1.7 billion for T2D were calculated. Total savings were generally larger among adults of lower socioeconomic status and those with lower dietary fibre intakes. Given the substantial healthcare expenditure and productivity cost savings that could be realised through increases in cereal fibre, there is cause for the development of interventions and policies that encourage an increase in cereal fibre intake in Australia.